AKTUALISASI NILAI FILOSOFI TRI HITA KARANA DI LEMBAGA PERKREDITAN DESA (LPD) KESIMAN - Wijaya, I Gede Wisnu Darma; Suryanata, I Gusti Ngurah Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
ABSTRACT   This study aims to explore the embodiment of the Tri Hita Karana philosophical values. The case study was conducted at the Kesiman Village Credit Institution (LPD). To answer the research questions, interviews were conducted with informants to understand the actualization of the philosophical values ??of Tri Hita Karana . The data analysis technique in this study was carried out in four steps: data collection, data reduction, data display and conclusion drawing / verification. The data validity test in this qualitative research includes credibility test, data triangulation, member check, confirmability (objectivity) data. The results showed that: First, the Kesiman Village Credit Institution (LPD) has become a financial institution that has a positive impact on the behavior of the Kesiman traditional village which improves economic and social welfare. Second, the Kasiman Village Credit Institution (LPD) understands the value of the Tri Hita Karana philosophy and uses it as the basis for the organization's operations for the surrounding community. Third, the Kesiman Village Credit Institution (LPD) can consistently serve the community through the values ??of Tri Hita Karana (namely Parahyangan, Pawongan and Palemahan ) to embody the philosophical values ??of Tri Hita Karana .